An extension algorithm of regional eigenvalue assignment controller design for nonlinear systems - Arıcan, Ahmet Çağrı; Çopur, Engin Hasan; Inalhan, Gokhan; Salamci, Metin Uymaz (MDPI, 2023)
This paper provides a new method to nonlinear control theory, which is developed from the eigenvalue assignment method. The main purpose of this method is to locate the pointwise eigenvalues of the linear-like structure built by freezing the nonlinear systems at a given time instant in a desired disk region. Since the control requirements for the transient response characteristics are the major constraints on the selection of the disk centre and radius, two different update algorithms are also developed to reshape the disk region by changing the disk centre and radius at each time step. The effectiveness of the proposed methods is tested in both simulations and experiments. A validated three-DOF laboratory helicopter is used for experiments.
Keywords: regional eigenvalue assignment; robust control; nonlinear systems; transient response; stability margin; real-time control; 3-DOF helicopter